Proteomes of primary skin fibroblasts from healthy individuals reveal altered cell responses across the life span. Issue 5 (15th April 2022) - Tsitsipatis, Dimitrios; Martindale, Jennifer L.; Ubaida‐Mohien, Ceereena; Lyashkov, Alexey; Yanai, Hagai; Kashyap, Amogh; Shin, Chang Hoon; Herman, Allison B.; Ji, Eunbyul; Yang, Jen‐Hao; Munk, Rachel; Dunn, Christopher; et al.
Abstract: Changes in the proteome of different human tissues with advancing age are poorly characterized. Here, we studied the proteins present in primary skin fibroblasts collected from 82 healthy individuals across a wide age spectrum (22–89 years old) who participated in the GESTALT (Genetic and Epigenetic Signatures of Translational Aging Laboratory Testing) study of the National Institute on Aging, NIH. Proteins were extracted from lysed fibroblasts and subjected to liquid chromatography‐mass spectrometry analysis, and the expression levels of 9341 proteins were analyzed using linear regression models. We identified key pathways associated with skin fibroblast aging, including autophagy, scavenging of reactive oxygen species (ROS), ribosome biogenesis, DNA replication, and DNA repair. Changes in these prominent pathways were corroborated using molecular and cell culture approaches. Our study establishes a framework of the global proteome governing skin fibroblast aging and points to possible biomarkers and therapeutic targets. Abstract : The proteins expressed in different cell types with advancing human age are poorly characterized. Here, we used mass spectrometry to study the proteins present in primary skin fibroblasts collected from 82 healthy individuals across a wide age spectrum. We identified and validated key pathways changing with skin fibroblast aging, including autophagy, scavenging of reactive oxygen species, ribosome biogenesis, and DNA replication and repair.